M157. A MULTICENTRE STUDY OF 1H-MRS BRAIN GLUTAMATE LEVELS IN SCHIZOPHRENIA; INVESTIGATING THE EFFECT OF ANTIPSYCHOTIC MEDICATION, SYMPTOM SEVERITY AND AGE. (18th May 2020) - Merritt, Kate; Aleman, André; Block, Wolfgang; Bloemen, Oswald; Borgan, Faith; Bustillo, Juan; Capizzano, Aristides; Coughlin, Jennifer; de la Fuente-Sandoval, Camilo; Demjaha, Arsime; Do, Kim; Drost, Dick; et al.
Abstract: Background: Proton Magnetic Resonance Spectroscopy (1H-MRS) studies indicate that altered brain glutamate signalling contributes to the pathophysiology of schizophrenia and treatment response. However it is unclear whether clinical and demographic factors affect glutamate levels in the brain. Here we aim to determine the effects of age, antipsychotic medication, symptom severity and duration of illness on levels of glutamatergic metabolites and creatine, in a large multicentre dataset of patients with schizophrenia and healthy volunteers. Methods: Authors of 1H-MRS studies in schizophrenia were contacted between January 2014 and August 2017 and asked to provide individual glutamate, Glx, glutamine and creatine values alongside demographic and clinical data. Forty-five 1H-MRS studies contributed data to the multicentre dataset, and data was available from 1194 healthy volunteers and 1526 patients with schizophrenia and those at high risk of developing psychosis. Results: Age was associated with reduced glutamate levels in the medial frontal cortex, but the effect of aging was not accelerated in patients compared to healthy volunteers. Higher glutamate and Glx in the medial frontal and temporal lobes were associated with more severe symptoms, whereas Glx in subcortical regions, specifically the thalamus and striatum, did not relate to symptom severity. In the medial frontal cortex and striatum, exposure to antipsychotic medication was associated with lower levels of glutamatergic metabolites. Duration of illness was not associated with glutamatergic metabolites. Lastly, creatine in the medial frontal cortex and thalamus increased with age. Discussion: These data suggest that future 1H-MRS studies should control for the effects of age, symptom severity, and antipsychotic medication exposure. Caution is needed when using creatine as a reference to scale metabolites.